Revitalization of The Kota Tua Area in Supporting Sustainable Tourism in the Cirebon District - Kardiyati, Endah Nurhawaeny; Muhamad, M. (Golden Ratio of Mapping Idea and Literature Format, 2025)
The revitalization and rejuvenation of Kota Tua really requires the role of local government stakeholders in a sustainable manner. This research aims to see how the implementation of the revitalization has an interest in maintaining the cultural heritage of the city, preserving historical values, while developing urban sectors according to their economic potential. This research is located in Kota Tua Jamblang in Cirebon Regency, an old area that has been around since the 12th century. The research method uses descriptive qualitative data analysis techniques that emphasize observing phenomena based on facts in the field and assessing them briefly and quickly by developing indicators of sustainable tourism development. The results of the management discussion in destinations related to indicators: Management System to Protect Historic Buildings, Management System to Protect Culture and Arts, Management System to Protect Historic Buildings, Integrated and Integrated Monitoring System, and Level of Community Participation in Preserving Kawasam Old Town Jamblang. Each has its own level of importance and level of quality in the Jamblang district, Cirebon Regency, which varies. The revitalization and rejuvenation of Kota Tua has a high level of importance and quality in Cirebon Regency.